The Effectiveness of Individual Passing and Face-to-Face Passing Training Exercises on Increasing Motivation of Junior Football Athletes - Akbar, Muhammad Hilmi; Ridlo, Azi Faiz; Bujang; Riyadi, Dani Nur (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Passing is an important basic skill in football that affects the effectiveness of the game and teamwork. However, low motivation in basic technique training such as passing is an obstacle in the development of young athletes' abilities. This study aims to analyze the effectiveness of individual passing and face-to-face passing training on increasing the training motivation of junior football athletes. The research design used a quasi experiment with a pretest–posttest approach two groups design. The subjects of the study were 24 junior football athletes aged 13–15 years who were divided into two groups. The motivation instrument uses a validated exercise motivation questionnaire. Data analysis was conducted using paired t-test and independent t-test. The results showed a significant increase in motivation in both groups, with the passing group facing off showed a higher increase (p < 0.05). These findings suggest that social interaction in face-to-face training can strengthen the motivational aspects of young athletes.